Justice and Utility in the Settlement of “Klacht Delict” through Mediation: Concept and Impact in Aceh - Husin, Muhammad; Syahrin, Alvi; Din, Mohd.; Ilyas, Ilyas (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
This article examines the process of settlement of criminal cases of whole complaints resolved in Aceh through mediation. The settlement of “klacht delict (delik aduan)” cases in Aceh is practiced in the customary law society by directing the Qanun Aceh. The main focus of this study is the process of its completion, the legal effectiveness of the concept of mediation, as well as consideration of aspects of the legal purpose of the mediation process. This study uses empirical juridical methods which are analyzed using a restorative justice approach and legal sociology. Data was collected by conducting in-depth interviews and document studies. The results of the research showed that the criminal complaints settled by mediation with the non-litigation pattern practiced by law enforcement and the community in Aceh have met the legal objectives, including the aspects of utility and justice. This model of settlement has met the requirements of usefulness and justice for perpetrators and victims and is considered complete, so the case has not proceeded to the stage of investigation and is not passed on to the prosecution. Nevertheless, the settlement through mediation is not satisfied from the point of view of legal certainty, as the general criminal gap must not be resolved by mediation. Sociologically, this legal rule has an impact on society regarding criminal complaints that are resolved through mediation through non-litigation and are never again demanded for a law enforcement process regarding the results of the mediation which has been stated in the peace deed. So mediation has an impact on the realization of peace and order in society.